Framing and frame shifting in a higher education merger - Pick, David (Kluwer Academic Publishers, 2003)
Late in 1996, Kalgoorlie College and the Western Australian School of Mines inWestern Australia were merged to form an expanded campus of Curtin University, based in the state capital city of Perth. This paper uses a frame analytical approach to examining how differing and competing interpretations and commitments affected how the merger was played out. Three important frames, each of which had a major influence on the merger for periods of time are identified: one that emphasised regional social and economic development, another centred on education for industry and a third based on economic rationalism. This analysis connects changes in the direction of the merger to shifts in the way the merger was framed.